Direct Organogenesis of Different Explants of Aceh Patchouli (Pogostemon cablin Benth.) with Several BAP Concentrations - Prayoga, Mohammad Candra; Soeparjono, Sigit; Dewanti, Parawita; Handoyo, Tri; Hardjo, Popy Hartatie; Restanto, Didik Pudji (Universitas Negeri Semarang, 2024)
The patchouli plant (Pogostemon cablin Benth.) is a tropical herbaceous plant that produces essential oil. One of the problems is that the production is not yet optimal. Fulfillment of superior seedlings can help increase patchouli productivity. Conventional patchouli propagation through stem cuttings is ineffective and takes longer. Patchouli propagation can be done using a tissue culture approach via direct organogenesis to produce seedlings quickly and efficiently. Effective patchouli propagation methods and successful acclimatization are very important to research to support the propagation and breeding of patchouli plants. The aim of this research was to determine the best of BAP concentration in direct organogenesis of leaf and stem explants. The research design used a completely randomized series of hormone BAP, it has 5 levels, namely 0 mg/L (as control), 0.25 mg/L, 0.50 mg/L, 0.75 mg/L, and 1.0 mg/L. The explants used were the leaves and stems of Aceh patchouli. Plantlets are acclimatized in compost media and covering treatment. Based on the results of observations, the best BAP concentration is 0.25 mg/L with the initial observation parameters of the early emergence of shoots, number of shoots, and length of shoots on leaf explants were 10 daps, 35.33 shoots, and 2.83 cm respectively. The use of leaf explants showed a better response compared to stem explants. Patchouli plantlets were successfully acclimatized and can adapt to the ex vitro environment using the covering method. Successful patchouli propagation and high acclimatization can help produce effective patchouli seeds.